A Rare Embryological Phenomenon: Kissing Nevus Incidence and Clinical Features: Poster Presentation - Observational Study - Resident - atika syafendra; mardijas efendi; hendrianti (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Kissing nevus is a condition where the nevus extends up to the lid margins, its edges touch or “kiss” when the eyelids are closed. Although commonly presenting at birth, there have been cases where it appeared in later life. This occurs due to a rare embryological phenomenon and thus only 30 cases have been reported worldwide until 2020. Meanwhile in M Djamil Hospital Padang we found 4 cases during 2020-2022. This paper is aim to present this so called rare cases in a modest way Methods : This is a descriptive study related to kissing nevus cases in M Djamil Hospital Padang during 2020-2022. We diagnosed it clinically based on ophthalmology examination. The data were collected into master table and being analyzed. We put patient’s identity (name, age, and gender), nevus location, size, gross anatomy of the nevus and surgical procedure Results : Four patients were discussed in this study. Most of the patients (75%) is a woman. We found more cases in the first 2 decades of life (50%). The predilection location is at the temporal eyelid (50%), it’s size is equal, both (10-19 mm and 20-29 mm) is 50%. In study we only found a melanotic lesion (100%). Most of the patient were treated with excision biopsy + skin flap (75%) Conclusion : The prevalence of kissing nevus in M Djamil Hospital is high. Kissing nevus mostly suffered by young women, most cases affected temporal eyelid, the size 10-29 mm so that skin flap is the most suitable surgical procedure